The Court Poet/Praise Singer in Wole Soyinka’s Death and the King’s Horseman and Ola Rotimi’s Ovonramwen Nogbaisi: a Critical Appraisal - Afolayan, Bosede Funke (Afrika Focus, 2019)
Oral artists are a common sight in traditional African societies and were most prominent in old empires such as Oyo, Benin, Songhai and Mali. They also existed in the Zulu empire, northern Nigeria and among the Akan in Ghana. Their place is integral to the social and political well-being of these empires. In the Oyo empire, court poets are known as Olohun-Iyo. They are called griots in Senegal and Mali and among the Akan of Ghana, they are called Kwadwumfo. Modern Nigerian dramatists such as Wole Soyinka and Ola Rotimi have appropriated the image and roles of the court poet in Death and The King’s Horseman and Ovonramwen Nogbaisi respectively. This paper defines who a court poet is, his role as a maker and wordsmith, and the nature of his work and patronage. It examines the qualities he must possess and the content of his poetry. In examining the place of memory and remembering in the discharge of the poet ́s duties, the paper investigates the various mnemonic and retrieval systems used by the poet to recall past accounts and great deeds of the kings. The roles of traditional court poets will be compared with the roles played by Olohun-iyo and Uzazakpo in the selected plays. The paper will also discuss what has become of oral artists in modern African societies. How viable is the art-form in the modern world with the advent of technology? Has civilization and modernity eroded their importance in society? While affirming their traditional advisory, prophetic, warning, motivational roles and as repositories of customs and culture, this paper concludes by stating the poet employs linguistic, para- linguistic and “medicinal” strategies to recall events at a given performance. KEYWORDS: COURT-POET, PRAISE SINGER, TRADITIONAL AFRICAN POETRY, WOLE SOYINKA, OLA ROTIMI